2018
DOI: 10.1055/s-0036-1591544
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Oxidative C(sp3)–N Coupling by HBr and DMSO: A Novel Synthesis of 2,3-Dihydroquinazolin-4(1H)-ones

Abstract: A metal-free oxidative C(sp3)–N coupling process has been developed for the synthesis of 2,3-dihydroquinazolin-4(1H)-ones. The reaction between primary amines, isatoic anhydride, and benzylic alcohols in the presence of HBr in DMSO at 80 °C affords 2,3-dihydroquinazolin-4(1H)-ones in excellent yields. Under these reaction conditions, benzylic alcohols react with in situ generated bromodimethylsulfonium bromide to form alkoxysulfonium intermediates. These intermediates undergo an oxidative cyclization reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Rezaei et al reported the preparation of 2,3-dihydroquinazolin-4(1H)-ones in superb yields at 80 °C via metal-free oxidative C(sp3)-N coupling through the three-component reaction of primary amines, isatoic anhydride, and benzylic alcohols by using a combination of HBr and DMSO (Scheme 36). [45] Benzylic alcohols were successfully react with in situ generated bromodimethylsulfonium bromide to yield alkoxysulfonium intermediates under these reaction conditions. The generated intermediates further undergo an oxidative cyclization reaction with primary amines and isatoic anhydride to form the desired products.…”
Section: Metal-free Oxidative C(sp3)-n Couplingmentioning
confidence: 99%
“…Rezaei et al reported the preparation of 2,3-dihydroquinazolin-4(1H)-ones in superb yields at 80 °C via metal-free oxidative C(sp3)-N coupling through the three-component reaction of primary amines, isatoic anhydride, and benzylic alcohols by using a combination of HBr and DMSO (Scheme 36). [45] Benzylic alcohols were successfully react with in situ generated bromodimethylsulfonium bromide to yield alkoxysulfonium intermediates under these reaction conditions. The generated intermediates further undergo an oxidative cyclization reaction with primary amines and isatoic anhydride to form the desired products.…”
Section: Metal-free Oxidative C(sp3)-n Couplingmentioning
confidence: 99%
“…In 2018, Ranjbar et al. developed oxidative C(sp 3 )−N coupling using bromodimethylsulfonium bromide generated from the combination of HBr and DMSO (Scheme 1A) [3b] . However, in these recent advances, a stoichiometric amount of oxidants is still required.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, serious issues hinder the development in this field, such as the fact that the commercialized aldehydes used in the synthesis of these two heterocyclic compounds are of poor stability for being oxidizable and easy to be hydrolyzed or polymerized, giving rise to low efficiency. 23 On this account, cheap and easily available alcohols are assumed to be oxidized to aldehydes in situ through the "one-pot" continuous chemical conversion during the condensation reaction to synthesize heterocyclic compounds proposing a problem-solving strategy; thus, the alde-hydes with a complex production process can be omitted, which is in accordance with the principle of green synthesis. 24 Here, POM-based organocatalysts possess enormous eligibility for the design concept of desirable green and efficient catalysts.…”
Section: Introductionmentioning
confidence: 99%